Identification of a New Class of Lipid Droplet-Associated Proteins in Plants(1)([C])([W])([OPEN]) - Horn, Patrick J. (American Society of Plant Biologists, 2013)
Lipid droplets in plants (also known as oil bodies, lipid bodies, or oleosomes) are well characterized in seeds, and oleosins, the major proteins associated with their surface, were shown to be important for stabilizing lipid droplets during seed desiccation and rehydration. However, lipid droplets occur in essentially all plant cell types, many of which may not require oleosin-mediated stabilization. The proteins associated with the surface of nonseed lipid droplets, which are likely to influence the formation, stability, and turnover of this compartment, remain to be elucidated. Here, we have combined lipidomic, proteomic, and transcriptomic studies of avocado (Persea americana) mesocarp to identify two new lipid droplet-associated proteins, which we named LDAP1 and LDAP2. These proteins are highly similar to each other and also to the small rubber particle proteins that accumulate in rubber-producing plants. An Arabidopsis (Arabidopsis thaliana) homolog to LDAP1 and LDAP2, At3g05500, was localized to the surface of lipid droplets after transient expression in tobacco (Nicotiana tabacum) cells that were induced to accumulate triacylglycerols. We propose that small rubber particle protein-like proteins are involved in the general process of binding and perhaps the stabilization of lipid-rich particles in the cytosol of plant cells and that the avocado and Arabidopsis protein members reveal a new aspect of the cellular machinery that is involved in the packaging of triacylglycerols in plant tissues.